The Influence of Competence and Work Motivation on Employee Performance with Workload as an Intervening Variable in the Hybrid Work Era at the Secanggang Sub-District Office - Muhammad Hirzi; Muhammad Isa Indrawan; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aimed to examine the effects of competence and work motivation on employee performance, with workload as an intervening variable, at the Secanggang Sub-District Office, Langkat Regency, North Sumatra, Indonesia. The study employed a quantitative associative design and included all 82 employees as respondents through saturated sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS version 3.3.3. The measurement model demonstrated satisfactory validity and reliability, with all indicators meeting the thresholds for convergent and discriminant validity and Composite Reliability values exceeding 0.70. Structural model evaluation revealed that competence (β = 0.989; t = 168.917; p < 0.001) has a positive and significant effect on employee performance, indicating that higher competence—encompassing knowledge, skills, and work abilities—leads to improved performance. In contrast, work motivation does not have a significant direct effect on performance (β = −0.006; t = 0.326; p > 0.05). Additionally, neither competence nor motivation significantly influence workload, and workload was not found to mediate the relationships between competence or motivation and employee performance. These findings suggest that employee performance improvement occurs primarily through direct effects of competence rather than via workload or motivation. The study highlights that workload is largely determined by external factors such as organizational policies, task allocation, and work system design. Managerial implications indicate that enhancing employee performance in hybrid work environments should prioritize the development of employee competence through training, skill enhancement, and continuous professional capacity building. Overall, this study emphasizes competence as the key determinant of employee performance in the public sector, while work motivation and workload have limited influence.